2014
DOI: 10.2478/jppr-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of some medicinal plants for their allelopathic potential against redroot pigweed (Amaranthus retroflexus)

Abstract: Abstract:The study was conducted to determine the allelopathic effects of Crocus sativus L., Ricinus communis L., Nicotiana tabacum L., Datura inoxia Mill., Nerium oleander L., and Sorghum vulgare L. on the germination and growth of Amaranthus retroflexus (redroot pigweed).Powder and aqueous extracts of these plants were used to run the experiment under laboratory and greenhouse conditions. In the laboratory, all aqueous extracts showed a significant inhibitory effect on the germination, seedling length and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Similarly, Petri dish and pot experiments as well as type of extraction of allelochemicals from plant biomass differed in their inhibitory effect. Application of extracts in petri dishes generally had higher phytotoxic effect compared to plant residues in soil probably as a result of direct contact of seeds with extracts on filter paper , Nekonam et al, 2014 and diffusion and adsorption of allelochemicals in the soil (Vidal et al, 1998). However, differences among plant residues and extracts from fresh biomass depended on the plant species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Petri dish and pot experiments as well as type of extraction of allelochemicals from plant biomass differed in their inhibitory effect. Application of extracts in petri dishes generally had higher phytotoxic effect compared to plant residues in soil probably as a result of direct contact of seeds with extracts on filter paper , Nekonam et al, 2014 and diffusion and adsorption of allelochemicals in the soil (Vidal et al, 1998). However, differences among plant residues and extracts from fresh biomass depended on the plant species.…”
Section: Resultsmentioning
confidence: 99%
“…For example, lovage residues and chamomile extracts had higher inhibitory potential compared to lovage extracts and chamomile residues. According to Nekonam et al (2014) some plant species have stronger inhibitory effect when applied as residues as a result of stronger extraction of allelochemicals during residues decomposition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth of the two target plant species in the presence of M. pigra leaf samples at different concentrations indicated the response was species-specific and concentration-dependent as well as depending on the properties of the allelochemicals. Nekonam et al (2014) suggested that variability in allelopathic expression in a plant might be due to the different nature of allelochemicals released by the species. There are various direct modes of action of allelochemicals on plant growth and metabolism, cell division, cell elongation, membrane permeability, mineral uptake, photosynthesis, respiration and specific enzyme activity, whereas there are indirect effects on soil properties and nutrient cycling (Rice, 1984;Weir et al, 2004;Farooq et al, 2013;Hernández-Aro et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction resulting from Eucalyptus leaf compost is more severe. Sabagh Nekonam et al (2014) studied the allelopathic effects of Crocus sativus L., Ricinus communis L., Nicotiana tabacum L., Datura inoxia Mill., Nerium oleander L., and Sorghum vulgare L. on the germination and growth of Amaranthus retroflexus L. (redroot pigweed). All aqueous extracts showed significant inhibitory effects on the germination, seedling length and weight of redroot pigweed plants under laboratory conditions and extracts and the powder of these plants showed significant inhibitory effects on pigweed dry weight, height, leaf area, the number of survivor plants, and the amount of chlorophyll under greenhouse conditions.…”
Section: Discussionmentioning
confidence: 99%